2004
DOI: 10.1590/s0100-879x2004001200012
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng administration protects skeletal muscle from oxidative stress induced by acute exercise in rats

Abstract: Enzymatic activity was analyzed in the soleus, gastrocnemius (red and white) and plantaris muscles of acutely exercised rats after long-term administration of Panax ginseng extract in order to evaluate the protective role of ginseng against skeletal muscle oxidation. Ginseng extract (3, 10, 100, or 500 mg/kg) was administered orally for three months to male Wistar rats weighing 200 ± 50 g before exercise and to non-exercised rats (N = 8/group). The results showed a membrane stabilizing capacity of the extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 36 publications
3
29
0
2
Order By: Relevance
“…Mechanical stress caused by eccentric exercise disturbs the ultrastructural integrity of skeletal muscle fibers (12), resulting in an acute inflammatory response where neutrophils and macrophages infiltrate skeletal muscle cells, generating reactive oxygen species (ROS), including free radicals. It has been shown that ginseng intake lowers inflammatory markers (6) and protects against inflammation after eccentric exercise (13), as such, ginseng may prevent muscle damage by reducing inflammation. Furthermore, the increase of ROS in exercise has been implicated in muscle fatigue and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical stress caused by eccentric exercise disturbs the ultrastructural integrity of skeletal muscle fibers (12), resulting in an acute inflammatory response where neutrophils and macrophages infiltrate skeletal muscle cells, generating reactive oxygen species (ROS), including free radicals. It has been shown that ginseng intake lowers inflammatory markers (6) and protects against inflammation after eccentric exercise (13), as such, ginseng may prevent muscle damage by reducing inflammation. Furthermore, the increase of ROS in exercise has been implicated in muscle fatigue and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that dietary antioxidants may prevent muscle damage by scavenging ROS produced during exercise (15,16). It is possible that ginseng and dietary antioxidants might have similar function; Korean red ginseng contains the major antioxidant enzyme, Rb2 (17), which scavenges hydroxyl radicals and protects unsaturated fatty acids from oxidation (13).…”
Section: Discussionmentioning
confidence: 99%
“…Exhaustive exercise-induced oxidative stress may result in muscle fatigue, muscle damage, and a reduction in physical performance [8]. Several studies have indicated that dietary antioxidants may prevent exercise-induced oxidative damage, as they are able to detoxify a number of peroxides directly through scavenging ROS that are generated during exercise or indirectly as modulators of intracellular pro-and anti-oxidant enzymes [9].…”
Section: Introductionmentioning
confidence: 99%
“…인삼의 페놀성 성분들은 노화억제 에 유효성분으로 10여종 이상의 항산화성, 페놀성 물질들이 밝혀졌고, 이들은 고혈압억제, 항암, 항산화, 미백활성 등의 생리활성으로도 알려져 있으며 [3][4][5] , 또한 다양한 스트레스에 대 해 비특이적으로 육체적, 정신적 안정 상태를 유지시킨다 6) . 고려 인삼의 항 스트레스 효과는 격한 운동 [7][8] , 수영 9) , 또는 저온에서 수영 [10][11] , 고정화 . .…”
unclassified